Strategies for recruitment and retention of diverse and underserved cancer survivor and caregiver dyads in clinical trials - Mary Hadeed; Terry A. Badger; Chris Segrin; Rogelio Robles-Morales; Samantha J. Werts-Pelter (Contemporary Clinical Trials Communications)
Background: Cancer survivor-caregiver dyads from underrepresented racial and ethnic groups and those with lower socioeconomic status are less likely to participate in clinical research. Sociocultural and socioeconomic barriers perpetuate health inequity and increase disparities in cancer care. Purpose: We describe our systematic approach to recruiting and retaining diverse survivor-caregiver dyads in supportive cancer care studies. Methods: Matsuda's research recruitment guidelines of evaluate, engage, reflect, and carefully match (“EERC”) were adapted and applied through a framework of six guiding principles. Results: A systematic approach to recruitment of underrepresented dyads in cancer support research includes 1) Developing a bilingual, bicultural study team with shared language and culture of the study population, 2) Ensuring team members share a passion for cancer health equity and are trained with a community-centric approach, 3) Designing accessible interventions, study materials, and shared data collection tools across similar studies with community and stakeholder input, 4) Engaging local and regional stakeholders with expertise of health disparities among the catchment area, 5) Partnering with Community Health Workers (CHWs) and gatekeepers to enhance community presence, and 6) Ensuring careful application of matching study team members and participants beyond race and ethnicity to prioritize the cultural values and social factors that impact cancer survivors and caregivers. Conclusion: Applying a systematic approach to recruiting and retaining underrepresented dyads in cancer research can potentially reduce sociocultural and socioeconomic barriers to cancer health equity.